Spiritual Art: A Study of Illuminated Drawings - Kateb, Fatemeh (Journal of History Culture and Art Research, 2017)
Illumination can be seen as a collection of exquisite and novel designs that painters and illumination-workers use to make religious, scientific, cultural, historical, and other collections of work beautiful. The professionals of illumination use these techniques in books to beautifully virtualize the golden pages of the eternal literature and the religious texts of their homeland. In this way, the sides and margins of the pages are decorated with designs of Islimi (arabesque) branches, stems, flowers, and Cathay (Khataei) leaves. Illuminations like paintings have various schools and periods, such as the Seljuk, Bukhara, Timurid, Safavid, Qajar schools, with further branches within each school. The illuminations of different periods represent the states and spirits of those eras. However, the illustrated paintings have been performed in the primary state in each school and era with some minor differences in colors and designs, and it can be said that the basis of the illustrated designs are three geometric shapes of the square, circle and triangle, and the combination of these three shapes. In this article, we try to study illumination drawings in terms of the spiritual dimension and its effect on the soul and psych. Furthermore; we will study the spiritual nature of the motifs in order to achieve a deeper understanding of the spirit of Islamic art.